Definitions of Life Style and its Application to Travel Behavior - Uth, Thyra C. (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
The concept of life style is increasingly applied to the area of transportation. Yet, at the same time it is theoretically ambiguous and generally ill-defined. In this paper definitions of life style will be discussed in order to find a useful definition of the concept of life style and in order to explore its claimed relationship with travel behavior. This clarification of the life style concept will be achieved by means of a literature review.